Clinical Profile and Outcomes of Geriatric Patients Admitted to Level III Intensive Care Unit of a Tertiary Care Hospital of Nepal: A Retrospective Observational Study - Piya, Buna; Koirala, Sabin; Adhikari, Suraj; Karki, Arjun (Journal of Nepalese Society of Critical Care Medicine, 2026)
Background and aims: Ageing global population results in an increasing burden of critically ill elderly patients requiring intensive care. Data on clinical characteristics and outcomes of geriatric patients in intensive care unit (ICU) of Nepal is limited. This study aimed to evaluate the clinical profile and outcomes of geriatric patients admitted to a level III ICU of a tertiary care hospital in Nepal. Methods: This retrospective observational study was conducted using registry data from the Nepal Intensive Care Research Foundation (NICRF). Patients aged ≥60 years admitted to the ICU of the Hospital of Advanced Medicine and Surgery (HAMS) between April 1, 2024, and March 31, 2025, were included in the study. Patients with incomplete data or ICU stay <24 hours were excluded. Demographic characteristics, comorbidities, admission patterns, organ support requirements, and outcomes were studied. Results: A total of 437 geriatric patients were included, representing 56.9% of total ICU admissions. The mean age was 74.6±8.7 years. Most admissions occurred through the emergency department (68.4%) and were medical cases (86.5%). Mechanical ventilation was required in 14.1% of patients, vasopressors in 19.4%, and renal replacement therapy in 1.4%. The median ICU length of stay was 3 days (IQR 2–5). Overall ICU mortality was 6.2% (n=27). Conclusion: Geriatric patients constituted a substantial proportion of ICU admissions in this tertiary care center. Although comorbidity burden was high, overall outcomes were comparable to younger age groups suggesting that clinically meaningful outcomes can be achieved in elderly critically ill patients with appropriate utilization of ICU resources.